A utilização pela controladoria dos trabalhos da auditoria interna e externa sobre o sistema de controle interno: um estudo nas grandes empresas do estado do Ceará - Araújo, Paolo Giuseppe Lima de (2006)
The purpose of this research is to investigate the main objectives which the Controllership uses the services developed by the internal and external auditing concerning internal control, focusing on the biggest companies in the state of Ceará. For its accomplishment a field research was made in companies listed in the Prêmio Delmiro Gouveia, 2004 edition, with revenue over the R$ 100 million, in order to identify the Controllership organization and attributions, the internal control structures and its attributions, and also the different type of services developed by the internal and external auditing, regarding the internal control system. This paper is organized in two fields: first, a bibliographical research on controllership, internal control, internal and external auditing; and second, the analysis of the field research. The results found show that the Controllership uses the services developed by the internal and external auditing concerning internal control with the following objectives: monitor the internal control system; identify and quantify frauds; know the reason why the identified mistakes occur and to improve the system in use.